2015
DOI: 10.11138/ads/2015.6.3.104
|View full text |Cite
|
Sign up to set email alerts
|

A tooth preparation technique in fixed prosthodontics for students and neophyte dentists

Abstract: A tooth preparation technique in fixed prosthodontics for students and neophyte dentists sonal experience with the novel technique. It could helps dental students and neophyte dentists in their learning curve.Key words: tooth preparation, fixed prosthodontics, dental education, prosthodontics. IntroductionTooth preparation for fixed prosthesis is a common procedure in clinical practice, which all general dentists should perform correctly. However, it could be difficult to obtain always a predictable result, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
0
15
0
5
Order By: Relevance
“…Teeth were lightly prepared as a slice preparation with no finish line cervically. The external walls were cut to be parallel with a maximum wall inclination of 6 ᵒ -14 ᵒ on buccal, lingual, and proximal aspects [41,42] creating a total occlusal convergence (TOC) of 10 ᵒ -20 ᵒ [43,44]. The inclination angles formed was determined by direct viewing of the preparation from all aspects (buccal, lingual and proximal).…”
Section: Methodsmentioning
confidence: 99%
“…Teeth were lightly prepared as a slice preparation with no finish line cervically. The external walls were cut to be parallel with a maximum wall inclination of 6 ᵒ -14 ᵒ on buccal, lingual, and proximal aspects [41,42] creating a total occlusal convergence (TOC) of 10 ᵒ -20 ᵒ [43,44]. The inclination angles formed was determined by direct viewing of the preparation from all aspects (buccal, lingual and proximal).…”
Section: Methodsmentioning
confidence: 99%
“…Mientras más paralelas son las paredes axiales, la retención es mayor. (10) Lo que se traduce en un ángulo de convergencia oclusal total menor con una preparación dentaria más conservadora. Sin embargo, preparaciones con paredes paralelas son dificultosas de lograr en boca sin el riesgo de crear escalones dentro de la misma.…”
Section: Introductionunclassified
“…However, it is difficult to achieve this parallelism without undercut creation. 16 Many studies showed a significant relation between total occlusal convergence and the retention and resistance of restoration on the prepared tooth. 17,18 The optimal total occlusal convergence ranged from two degrees to 5.5 degrees.…”
Section: Introductionmentioning
confidence: 99%